Sharia Peer to Peer Financing Innovation in Indonesia: Insights from Prospective Investors - Roisatun Kasanah; Sulistya Rusgianto (Universitas Islam Internasional Indonesia, 2026)
Sharia peer-to-peer (P2P) financing offers a sharia-compliant investment alternative that addresses increasing demand in Indonesia, with substantial growth potential. This study identifies the factors influencing investors' intentions to use sharia P2P financing services in Indonesia. Drawing on the theory of reasoned action and the extended valence framework, this research examines perceived benefit, perceived risk, trust, social influence, and sharia financial knowledge. This study seeks to enrich the literature on sharia investment by focusing on the psychological aspects of investors, particularly trust, perceived benefits, and perceived risks. Using a quantitative methodology and Partial Least Squares analysis, data were gathered from 219 respondents through online surveys. The results indicate that all variables, except perceived risk, significantly influence investment intention, with trust being the most impactful factor. These findings provide valuable insights for service providers and regulators to enhance investment activities through better understanding and strategic improvements.